Indonesian Sports Journalists' Existence and Professionalism in the Era of Digitalization and Media Convergence - Nurrachmad, Limpad; Junaidi, Said; Sumartiningsih, Sri; Pratama, Ade Bagus (Faculty of Sport and Health Sciences, 2024)
The ongoing advancement of technology in the era of digitalization has brought about significant transformations in all domains, including media. Multiple mass media corporations are vying to transition from traditional to digital systems in order to maintain their ability to compete and survive in the face of the increasing convergence of media. Media businesses are required to ensure that there are repercussions for delivering news in both hard news and soft news formats promptly, accurately, and engagingly. The purpose of this study is to investigate and describe the existence and professionalism of Indonesian sports journalists in the digitalization and media convergence era. The study was conducted using a qualitative approach. The six journalists were requested to express their experiences and perspectives by means of an open-ended questionnaire and semi-structured interviews. The gathered replies were subsequently examined utilizing the methodologies and instruments of Narrative analysis. In conclusion, sports journalists must be proficient in multimedia, able to swiftly adapt to new situations, have high moral standards, be able to interpret sports data, and be able to maintain their professionalism in the face of the challenges posed by the digital age and the convergence of media. Competitors will always find a way to beat out those lacking in soft skills and IT knowledge. Additionally, it is undeniable that sports writers cannot survive without engaging with audiences and sports fans via various internet platforms, including social media.